# How do you solve 3p - 1 = 5(p -1) - 2(7- 2p)?

Aug 2, 2018

By arranging the equation

#### Explanation:

$3 p - 1 = 5 p - 5 - 14 + 4 p$

after getting rid of parantheses.

Now collect p terms on the right-hand side and numbers on the other:

$- 1 + 5 + 14 = 5 p + 4 p - 3 p$

$18 = 6 p$

$\frac{18}{6} = p$

$3 = p$

The answer is $p = 3$

Aug 2, 2018

$p = 3$

#### Explanation:

$3 p - 1 = 5 \left(p - 1\right) - 2 \left(7 - 2 p\right)$

$3 p - 1 = 5 p - 5 - 14 + 4 p$, Removing bracelets.

$3 p - 5 p - 4 p = - 5 - 14 + 1$, bringing like terms together.

$- 6 p = - 18$, simplifying.

$p = \frac{- 18}{- 6} = 3$

Aug 2, 2018

$p = 3$

#### Explanation:

We can distribute the parenthesis on the right to get

$3 p - 1 = 5 p - 5 + 4 p - 14$

We can combine our like terms on the right to get

$3 p - 1 = 9 p - 19$

Next, let's add $1$ to both sides to get

$3 p = 9 p - 18$

Next, do get our variables on one side, let's subtract $9 p$ from both sides to get

$- 6 p = - 18$

Lastly, we can divide both sides by $- 6$ to get

$p = 3$

Hope this helps!